2002
DOI: 10.1262/jrd.48.309
|View full text |Cite
|
Sign up to set email alerts
|

Birth of Lambs after Direct Transfer of Vitrified Ovine Embryos.

Abstract: Abstract. The aim of this study was to investigate in vivo viability of vitrified ovine embryos after direct transfer using a laparoscope. In vivo-derived ovine morulae and blastocysts were equilibrated in 25% glycerol and 25% ethylene glycol solution, loaded into a heat-pulled straw and vitrified. Thirty-eight embryos were transferred into 19 recipients (2 embryos per recipient) and pregnancy was examined at 54-59 days after transfer. The pregnancy, implantation, lambing, and survival rates were 15.8% (3/19),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, our lower results could not be applied to human error because this experiment was performed by the same technical team, suggesting that the observed difference may be related to the interval between flushing and embryos transference (10-12 h) or to the different batches and breed of female recipients It is desirable that cryopreserved embryos are transferred into the uterus as soon as possible, and the interval between post-thawing and transference has a great influence on subsequent viability. In this experiment, the interval between flushing and cryopreservation was about 8 h. In addition to that, the stepwise for warming embryos requires a long time until the transference and the number of manipulations affect embryonic survival (Okada et al 2002). Dattena et al (2004) reported no difference about embryo viability if one or three stepwise warming dilution was employed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, our lower results could not be applied to human error because this experiment was performed by the same technical team, suggesting that the observed difference may be related to the interval between flushing and embryos transference (10-12 h) or to the different batches and breed of female recipients It is desirable that cryopreserved embryos are transferred into the uterus as soon as possible, and the interval between post-thawing and transference has a great influence on subsequent viability. In this experiment, the interval between flushing and cryopreservation was about 8 h. In addition to that, the stepwise for warming embryos requires a long time until the transference and the number of manipulations affect embryonic survival (Okada et al 2002). Dattena et al (2004) reported no difference about embryo viability if one or three stepwise warming dilution was employed.…”
Section: Discussionmentioning
confidence: 86%
“…It is desirable that cryopreserved embryos are transferred into the uterus as soon as possible, and the interval between post‐thawing and transference has a great influence on subsequent viability. In this experiment, the interval between flushing and cryopreservation was about 8 h. In addition to that, the stepwise for warming embryos requires a long time until the transference and the number of manipulations affect embryonic survival (Okada et al. 2002).…”
Section: Discussionmentioning
confidence: 99%